2019
DOI: 10.1186/s12870-019-1756-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of atemoya pericarp elucidates the role of polysaccharide metabolism in fruit ripening and cracking after harvest

Abstract: Background Mature fruit cracking during the normal season in African Pride (AP) atemoya is a major problem in postharvest storage. Our current understanding of the molecular mechanism underlying fruit cracking is limited. The aim of this study was to unravel the role starch degradation and cell wall polysaccharide metabolism in fruit ripening and cracking after harvest through transcriptome analysis. Results Transcriptome analysis of AP atemoya pericarp from cracking fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…In line to this, the high level of galacturonate in cracking-resistant cultivars (Fig. 4c) could also be advocated as a precursor compound for protopectin, which may contribute to early pectin formation [29].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In line to this, the high level of galacturonate in cracking-resistant cultivars (Fig. 4c) could also be advocated as a precursor compound for protopectin, which may contribute to early pectin formation [29].…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, overexpression of trehalose biosynthetic genes results in a more sensitive reaction of the stomatal guard cells and closing of the stomata under water stress conditions [28]. Interestingly, an up-regulation of several genes involved in trehalose metabolism has been observed in African Pride atemoya during various cracking stages [29]. Taking into account that the osmotic water uptake through the skin is an important factor for rain-induced sweet cherries cracking [30] along with the excellent capacity of trehalose to protect membranes and proteins from degradation [31], we assume that trehalose could not be only directly involved in cracking but can also regulate this process mediating the crosstalk with osmoprotectant-related compounds as, for example, with sugars [32].…”
Section: Discussionmentioning
confidence: 99%
“…In line to this, the high level of galacturonate in cracking-resistant cultivars (Fig. 4c) could also be advocated as a precursor compound for protopectin, which may contribute to early pectin formation [26].…”
Section: Physiological Traits and Skin Metabolites In Relations To Crmentioning
confidence: 67%
“…Indeed, overexpression of trehalose biosynthetic genes results in a more sensitive reaction of the stomatal guard cells and closing of the stomata under water stress conditions [25]. Interestingly, an up-regulation of several genes involved in trehalose metabolism has been observed in African Pride atemoya during various cracking stages [26]. Taking into account that the osmotic water uptake through the skin is an important factor for rain-induced sweet cherries cracking [27] along with the excellent capacity of trehalose to protect membranes and proteins from degradation [28], we assume that trehalose could not be only directly involved in cracking but can also regulate this process mediating the crosstalk with osmoprotectant-related compounds as, for example, with sugars [29].…”
Section: Physiological Traits and Skin Metabolites In Relations To Crmentioning
confidence: 99%
“…Fruit cracking is a complex physiological process that is controlled by numerous genes working together, rather than a single gene directly controlling the process [18,45]. Researchers have found that several cell wall modi cation genes, including β-GAL, β-GLU, PE, and PG are differentially expressed in cracked fruits compared with levels in non-cracking litchi fruits [21].…”
Section: Candidate Degs and Daps May Play Key Roles In Fruit Pericarpmentioning
confidence: 99%